Genetic fine-structural analysis of the Saccharomyces cerevisiae alpha-pheromone receptor. - Konopka, J B (1991)
The alpha-pheromone receptor encoded by the STE2 gene contains seven potential transmembrane domains. Its ability to transduce the pheromone signal is thought to require the action of a G protein. As an initial step toward defining the structural features of the receptor required for its activity, we examined the phenotypic consequences of linker insertion mutations (12 bp) at 10 different sites in the STE2 gene. Three mutant classes, which correspond to three different regions of the receptor protein, were observed. 1) The two mutants affecting the C-terminal region (C-terminal mutants) were essentially wild type for mating efficiency, pheromone binding, and pheromone sensitivity. 2) The three mutants in the N-terminus mated with reduced efficiency, showed reduced pheromone binding capacity, and were partially defective in pheromone induction of agglutinin production and cell division arrest. Increased gene dosage of these N-terminal alleles suppressed their mutant phenotypes, whereas the sst2-1 mutation, which blocks adaptation to pheromone, did not result in suppression. Thus, the N-terminal mutants were apparently limited by receptor production, but not by the adaptation function SST2. 3) The five mutants in the central region containing the seven transmembrane segments (central mutants) were completely defective for mating and did not respond to pheromone, but could be distinguished by their ability to bind pheromone. Inserts in or near transmembrane domains 2 and 4 blocked pheromone binding, whereas inserts into transmembrane domains 1, 5, and 6 retained partial pheromone binding activity even though they failed to transduce a signal. The central mutants were not suppressed by increased gene dosage, and one mutant (ste2-/101) was partially suppressed by sst2-1. Furthermore, the central core mutants were also distinguished from one another in that three of the five mutants were able to partially complement the temperature sensitivity of ste2-3.